Genuine four-partite Bell nonlocality in the curved spacetime - Guang-Wei Mi; Xiaofen Huang; Shao-Ming Fei; Tinggui Zhang (European Physical Journal C: Particles and Fields)
Abstract The quantum Bell nonlocality plays a crucial role in quantum information processing. In this paper, we first obtain the quantitative analytical expression of the genuine four-partite Bell nonlocality of any 4-qubit quantum state. Then, we investigate and derive the genuine four-partite nonlocalities in the background of the Schwarzschild black hole and the Schwarzschild–de Sitter spacetime. In the Schwarzschild black hole, it is shown that the Hawking effect destroys the accessible genuine four-partite nonlocality whif the Hawking effect of the Schwarzschild–de Sitter spacetime on the genuine four-partite nonlocality of massless Dirac fields.